Analisis UX pada Aplikasi E-Learning menggunakan Metode SUS (System Usability Scale) - Rahayu, Novi (Jurnal Komputer, 2025)
E-learning has become an essential need in education, especially accelerated by the COVID-19 pandemic. The implementation of online learning systems using Moodle-based Learning Management System (LMS), which requires evaluation to ensure its effectiveness and usability. This study aims to implement the System Usability Scale (SUS) method to measure the level of usability. This evaluation is expected to provide recommendations for improvements to improve the quality of online learning. Based on the existing problems, it explains how to implement the SUS method to measure usability in the e-learning system at UMM. The study was limited to usability evaluation using the SUS method without discussing other aspects such as learning content or other supporting technology infrastructure. The study used the SUS method which involved a questionnaire with 10 questions to assess usability aspects such as learning ability, efficiency, error rate, and user satisfaction. The analysis showed a fairly good level of usability but still needed some technical improvements such as system stability and ease of use. The implementation of the SUS method was effective, providing valuable insights for system improvements to improve the learning experience.